Mobile user experience : patterns to make sense of it all - Mendoza, Adrian (Morgan Kaufmann, an imprint of Elsevier, 2014)
This is your must-have resource to the theoretical and practical concepts of mobile UX. You'll learn about the concepts and how to apply them in real-world scenarios. Throughout the book, the author provides you with 10 of the most commonly used archetypes in the UX arena to help illustrate what mobile UX is and how you can master it as quickly as possible. First, you'll start off learning how to communicate mobile UX flows visually. From there, you'll learn about applying and using 10 unique user experience patterns or archetypes for mobile. Finally, you'll understand how to prototype and use these patterns to create websites and apps. Whether you're a UX professional looking to master mobility or a designer looking to incorporate the best UX practices into your website, after reading this book, you'll be better equipped to maneuver this emerging specialty. Addresses the gap between theoretical concepts and the practical application of mobile user experience designIllustrates concepts and examples through an abundance of diagrams, flows, and patternsExplains the differences in touch gestures, user interface elements, and usage patterns across the most common mobile platformsIncludes real-world examples and case studies for this rapidly growing field.
Keywords: mobilní aplikace; uživatelská rozhraní; grafická uživatelská rozhraní; vývoj softwaru; mobile applications; user interfaces; graphical user interfaces; software development; elektronické knihy; electronic books